Den of Thieves - Stewart, James B. (New York Simon & Schuster Paperbacks, 1992)
How four men--Michael Milken, Ivan Boesky, Martin Siegel, Dennis Levine--"nearly destroyed Wall Street ... how they made billions and how they got caught."
Include Illustrations, Chronology, Index, Notes and Sources.
Keywords: United States -- Insider trading in securities -- Investment banking--Corrupt practices